Pan Tadeusz; or, The last foray in Lithuania : a story of life among Polish gentlefolk in the years 1811 and 1812 - Mickiewicz, Adam, 1798-1855; Noyes, George Rapall, 1873-1952 (Salt Lake City, UT : Project Gutenberg, 2009)
"Pan Tadeusz; or, The Last Foray in Lithuania" by Adam Mickiewicz is an epic poem written in the early 19th century. The narrative unfolds against the backdrop of Polish gentlemen in Lithuania during the years 1811 and 1812, intertwining themes of nostalgia, national identity, and romanticism. The central characters include Thaddeus Soplica, a young gentleman returning home after his studies, and Jacek Soplica, his father, whose complex past weaves into the larger fabric of the tale. The opening of the story introduces us to the lush, pastoral landscape of Lithuania, where Thaddeus Soplica arrives at his family estate after a long absence. Filled with emotion, he reminisces about his childhood home, adorned with familiar sights and memories. As he explores his old mansion, he senses a mysterious presence and encounters a beautiful girl, hinting at the romantic developments to come. The ambiance is rich with tradition and local customs, setting the stage for the upcoming gatherings of family and friends, as well as the brewing tensions between the Soplica family and their neighbors amidst the larger political unrest in Europe. The opening establishes a poignant tone of longing for home and highlights the cultural nuances of the Polish gentry. (This is an automatically generated summary.)
Release date is 2009-03-02
Keywords: Gentry -- Lithuania -- Social life and customs -- 19th century -- Fiction; Gentry -- Poland -- Social life and customs -- 19th century -- Fiction; Epic poetry, Polish -- Adaptations